New techniques, new challenges-The dilemma of pain management for less invasive surfactant administration? - Ashanti Balakrishnan; Ranveer S. Sanghera; Elaine M. Boyle (Wiley, 2021)
Abstract Recent years have seen the increasing use of noninvasive respiratory support in preterm infants with the aim of minimizing the risk of mechanical ventilation and subsequent bronchopulmonary dysplasia. Respiratory distress syndrome is the most common respiratory diagnosis in preterm infants, and is best treated by administration of surfactant. Until recently, this has been performed via an endotracheal tube using premedication, which has often included opiate analgesia; subsequently, the infant has been ventilated. Avoidance of mechanical ventilation, however, does not negate the need for surfactant therapy. Less invasive surfactant administration (LISA) in spontaneously breathing infants is increasing in popularity, and appears to have beneficial effects. However, laryngoscopy is necessary, which carries adverse effects and is painful for the infant. Conventional methods of premedication for intubation tend to reduce respiratory drive, which increases the likelihood of ventilation being required. This has led to intense debate about the best strategy for providing appropriate treatment, taking into account both the respiratory needs of the infant and the need to alleviate procedural pain. Currently, clinical practice varies considerably and there is no consensus with respect to optimal management. This review seeks to summarize the benefits, risks, and challenges associated with this new approach.